Enabling deep-space experimentations on cyanobacteria by monitoring cell division resumption in dried Chroococcidiopsis sp. 029 with accumulated DNA damage - Fagliarone, Claudia; Mosca, Claudia; Di Stefano, Giorgia; Leuko, Stefan; Moeller, Ralf; Rabbow, Elke; Rettberg, Petra; Billi, Daniela (Frontiers in Microbiology, 2023)
Cyanobacteria are gaining considerable interest to support long-term human presence on the Moon and settlements on Mars due to their ability to produce oxygen and their potential as bio-factories for space biotechnology/synthetic biology applications. Since many unknowns remain in our knowledge to bridge the gap to move cyanobacterial bioprocesses from Earth to space, we investigated the cell division resumption upon rehydration of dried Chroococcidiopsis sp. CCMEE 029 that accumulated DNA damage while exposed to space vacuum, Mars-like conditions and Fe-ion radiation. Upon rehydration, the monitoring of the ftsZ gene showed that cell division was arrested until DNA damage was repaired and that this process required 48hrs under laboratory conditions. During the recovery, a progressive DNA repair lasting 48 hrs of rehydration, was revealed by PCR-stop assay. This was followed by an overexpression of the ftsZ gene, ranging from 7.5- to 9-fold compared to the non-hydrated samples. Knowing the time frame between DNA repair and cell division resumption is mandatory for deep-space experiments that are designed to unravel the effects of reduced/microgravity on this process. It is also required to meet mission requirements for dried-sample implementation and real-time monitoring upon recovery. No doubt future experiments within the lunar exploration mission Artemis and lunar Gateway station will help to move cyanobacterial bioprocesses beyond low Earth orbit. From an astrobiological perspective, these experiments will further our understanding of microbial response to deep-space conditions.